2021
DOI: 10.5194/egusphere-egu21-1828
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A New Mathematical Framework for Atmospheric Blocking Events

Abstract: <p>We use a simple yet Earth-like atmospheric model to propose a new framework for understanding the mathematics of blocking events, which are associated with low frequency, large scale waves in the atmosphere. Analysing error growth rates along a very long model trajectory, we show that blockings are associated with conditions of anomalously high instability of the atmosphere. Additionally, the lifetime of a blocking is positively correlated with the intensity of such an anomaly, against intuiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 93 publications
(149 reference statements)
2
21
0
Order By: Relevance
“…Hence it seems, to these authors, not to be possible to find a definition of regimes, using density or temporal persistence alone, that unifies all the systems we considered. While an alternative definition of regimes based on fixed points, UPOs or other 'exact solution' techniques might seem plausible, computing such solutions is extremely computationally demanding, and state-of-the-art techniques are only able to handle systems of significantly lower dimensionality than existing climate models [25]. More crucially, these techniques are inherently model features, in that they rely on being able to integrate the model dynamics.…”
Section: Why a Simpler Definition Of Regime Failsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence it seems, to these authors, not to be possible to find a definition of regimes, using density or temporal persistence alone, that unifies all the systems we considered. While an alternative definition of regimes based on fixed points, UPOs or other 'exact solution' techniques might seem plausible, computing such solutions is extremely computationally demanding, and state-of-the-art techniques are only able to handle systems of significantly lower dimensionality than existing climate models [25]. More crucially, these techniques are inherently model features, in that they rely on being able to integrate the model dynamics.…”
Section: Why a Simpler Definition Of Regime Failsmentioning
confidence: 99%
“…While a more technical definition based on exact solutions (e.g., fixed-points and periodic orbits) of the flow can work and even be computationally tractable for relatively low-dimensional systems [23,24], they suffer from the 'curse of dimensionality', and are generally limited to simple systems. In a state-ofthe-art application of these concepts to atmospheric modelling, [25] identified unstable periodic orbits (UPOs) corresponding to zonal and blocking events in a low resolution quasi-geostrophic model. However, the dimensionality of this model still sits well below that of weather and climate models, let alone the physical system itself.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the search for an attractor underlying turbulent flows in general, and geophysical turbulence in particular has however proved only partially successful. Since the 1990s several studies have suggested that the observed dynamical processes can be associated with the existence of non-hyperbolic strange and possibly stochastic attractors having a dimensionality much lower than the number of degrees of freedom of the system [23,24]. Non-hyperbolicity manifests itself with the fact that the attractor is heterogeneous in terms of its local properties of persistence and predictability [24,25].…”
mentioning
confidence: 99%
“…Since the 1990s several studies have suggested that the observed dynamical processes can be associated with the existence of non-hyperbolic strange and possibly stochastic attractors having a dimensionality much lower than the number of degrees of freedom of the system [23,24]. Non-hyperbolicity manifests itself with the fact that the attractor is heterogeneous in terms of its local properties of persistence and predictability [24,25]. When considering numerical models, this has important implications also in terms of error dynamics and efficiency of data assimilation [26].…”
mentioning
confidence: 99%
“…While a more technical definition based on exact solutions (e.g., fixed-points and periodic orbits) of the flow can work and even be computationally tractable for relatively low-dimensional systems [16,21], they suffer from the 'curse of dimensionality', and are generally limited to simple systems. In a stateof-the-art application of these concepts to atmospheric modelling, [32] identified unstable periodic orbits (UPOs) corresponding to zonal and blocking events in a low resolution quasi-geostrophic model. However, the dimensionality of this model still sits well below that of weather and climate models, let alone the physical system itself.…”
Section: Introductionmentioning
confidence: 99%